Isolated gastrointestinal symptoms as initial presentation in systemic lupus erythematosus and its differential diagnosis - Abd Latip, Nurul Akmal; Abdul Hadi, Azwanis; Ismail, Mohd Nizamuddin (Faculty of Medicine and Health Sciences, 2022)
Initial clinical presentation of Systemic Lupus Erythematosus (SLE) is varied as it affects various organs in the body. While the typical presentation of SLE is mucocutaneous, musculoskeletal and haematological manifestation, gastrointestinal (GI) manifestation is a rare initial presentation of SLE. We discuss the case of a 13-year-old girl who was diagnosed with SLE after she presented with isolated gastrointestinal symptoms. She presented with vomiting, diarrhoea, mild colicky abdominal pain and bilateral ankle oedema; and was treated as acute gastroenteritis. She returned after one week with worsening symptoms. Her full blood count showed bicytopenia; urinalysis had proteinuria and haematuria, and renal profile revealed acute on chronic kidney injury which triggered suspicions of a more serious disease rather than simple viral gastroenteritis. Further investigations of positive anti-nuclear antibody, low complements and positive Coombs’s test supported the diagnosis of SLE. The diagnosis of SLE was confirmed when her renal biopsy reported crescentic lupus nephritis ISN/RPS Class IV. Additional investigation to investigate the cause of her gastrointestinal symptoms included an ultrasound abdomen which showed minimal ascites and bilateral renal parenchymal disease. She was planned for colonoscopy but due to the unavailability of paediatric endoscopy, colonoscopy was postponed. However, her symptoms markedly improved with intravenous Cyclophosphamide which supported the diagnosis of GI SLE. This case report is to highlight that a patient with symptoms of simple viral gastroenteritis might have a more serious underlying disease. Even though rare, SLE can present with gastroenteritis symptoms and is one of the differential diagnoses that should be considered. Malaysian Journal of Medicine and Health Sciences (2022) 18(5): 218-221. doi:10.47836/mjmhs18.5.30